Dynamic mechanical writing of skyrmion-like polar nanodomains - Jaegyu Kim; Youngki Yeo; Yong-Jun Kwon; Juhyun Lee; Jeongdae Seo; Seungbum Hong; Chan-Ho Yang (npj Quantum Materials)
Abstract Ferroelectric materials exhibit a wealth of topological polar structures that hold promise for high-density, energy-efficient information technologies. Ferroelectric polarization configurations can be flipped by non-uniform mechanical stresses and associated lattice deformations and can be understood in the quasi-static regime based on flexoelectricity, but little is known about the dynamic mechanical excitations that generate topological ferroelectric structures. Here, we discover stable centre-type skyrmion-like polar nanodomains in super-tetragonal BiFeO3 thin films generated by vibrational tapping using scanning probe microscope tips. Vibrational tapping can bidirectionally switch out-of-plane polarization by exerting strong dynamic force onto the elastically soft state emerging from strain-driven morphotropic phase transitions, which may be attributed to unconventional non-linear flexoelectric effects in the large strain-gradient regime. Our study provides a novel pathway into not only dynamic mechanoelectric coupling and topological polar structures, but also dynamic mechanical excitation technologies applicable to various fields.